Faktor-faktor yang berhubungan dengan status gizi pada anak balita di Puskesmas Tandun 1 Kabupaten Rokan Hulu Provinsi Riau - Tuty Hertati Purba; Prita Delvia Yollanda; Wanda Lestari; Athira Demitri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Introduction; Toddlers need balanced nutrition so that their nutritional status is good, and the growth process is not hampered. The nutritional status of toddlers can be measured anthropometrically, anthropometric indices that are often used, namely: (weight/age), (height/age), and (weight/height). Objective; This study aimed to determine what factors are associated with the nutritional status of toddlers at Tandun 1 Health Center in Rokan Hulu Regency of Riau Province. Methode ;This is an observational research with a cross sectional study approach. The sampling was done by means of the Stratified Random Sampling Method. The population of this study was mothers who had toddlers aged 0-60 months and the sample in this study was mothers who had toddlers aged 24-60 months. The results of this study indicated that from the variable knowledge with a p value of 0.01 and food intake with a p value of 0.00 there was a significant relationship with a p value <0.05, while for the variable exclusive breastfeeding with a p value of 0.08 and a history of diarrhea with a p value of 0.74 there was no significant relationship with a p value> 0.05 in toddlers at Tandun 1 Health Center, Rokan Hulu Regency, Riau Province. It is expected that the health workers of the Health Center increase efforts to prevent nutritional status problems in toddlers which can be done such as providing information about good nutrition for toddlers and providing additional food to toddlers whose nutritional status is lacking.